2012
DOI: 10.1007/s11033-012-1727-4
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the cytotoxic T-lymphocyte antigen 4 gene and acute rejection risk in transplant recipients

Abstract: Cytotoxic T-lymphocyte antigen 4 (CTLA-4) gene polymorphisms have been reported to influence the risk for acute rejection (AR) in transplant recipients. However, the results still remain controversial and ambiguous. The objective of the current study was to conduct a meta-analysis investigating the association between polymorphisms in the CTLA-4 gene and the risk of AR in transplant recipients. Electronic searches for all publications were conducted on associations between this variant and acute rejection in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…The other area of interest, +49A/G, is found in exon‐1, gene polymorphisms in this site may change the cell surface expression of CTLA‐4 and have shown to be related to autoimmune disorders . In our study, we found + 49A/G genotype and G allelic variant to be unrelated to acute rejection risk, in harmony with a recent meta‐analysis that revealed no relations in most studies . The exceptions are the findings of Gendzekhadze et al.…”
Section: Discussionsupporting
confidence: 87%
“…The other area of interest, +49A/G, is found in exon‐1, gene polymorphisms in this site may change the cell surface expression of CTLA‐4 and have shown to be related to autoimmune disorders . In our study, we found + 49A/G genotype and G allelic variant to be unrelated to acute rejection risk, in harmony with a recent meta‐analysis that revealed no relations in most studies . The exceptions are the findings of Gendzekhadze et al.…”
Section: Discussionsupporting
confidence: 87%
“…However, these studies have yielded inconsistent results. 13,14 To produce more precise results, we evaluated these associations using a meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Although the development of acute rejection is complicated, its initiation requires both allorecognition and T‐cell activation (Ingulli, ; Wood & Goto, ). Genetic polymorphisms of MHC, costimulatory molecules, and cytokines genes, which involve in the allorecognition and the activation, have been proved to be associated with acute rejection in liver and renal transplantations (Bitetto et al., ; Jiang et al., ; Tapirdamaz et al., ; Zhu, Huang, Liu, & Xie, ).…”
Section: Discussionmentioning
confidence: 99%